Characterization of bacteriophage HN48 and its protective effects in Nile tilapia Oreochromis niloticus against Streptococcus agalactiae infections. Issue 10 (17th August 2018) - Luo, X; Liao, G; Liu, C; Jiang, X; Lin, M; Zhao, C; Tao, J; Huang, Z
Abstract: Streptococcus agalactiae is a causative agent responsible for massive mortalities of tilapia that has led to catastrophic losses to tilapia culture globally. Bacteriophages represent a new class of antimicrobials against bacteria. In this study, we characterized the bacteriophage HN48, which formed small and round‐transparent plaques on a double‐layer plate. With a hexagonal head and a long tail, this phage may belong to the Caudovirales according to the International Committee on Taxonomy of Viruses. HN48 was found to have a relatively wide and highly specific host range, to be sensitive to high temperature (60–80°C) and low pH (3–5), and to be relatively stable at alkaline pH (8–10). Intraperitoneal injection with HN48 had no adverse effects on tilapia and effectively inactivated the bacteria in the kidney. Fish that received phage therapy had 60% ± 3.3% survival rates and a delayed mean death time of about 3 days when compared to the control group. To the best of knowledge, this is the first study of tilapia streptococcal phage. Overall, the results indicated that phage HN48 could prevent tilapia from experimental S. agalactiae infection, suggesting it has the potential to control this disease.